Herbivores reduce seedling recruitment in alpine plant communities. (16th February 2021) - Opedal, Øystein H.; Nystuen, Kristin O.; Hagen, Dagmar; Holien, Håkon; Sørensen, Mia Vedel; Lang, Simone I.; Lindmo, Sigrid; Strimbeck, G. Richard; Graae, Bente J.
Abstract : Through changes in climate and other environmental factors, alpine tundra ecosystems are subject to increased cover of erect shrubs, reduced predictability of rodent dynamics and changes in wild and domesticated herbivore densities. To predict the dynamics of these ecosystems, we need to understand how these simultaneous changes affect alpine vegetation. In the long term, vegetation dynamics may depend critically on seedling recruitment. To study drivers of alpine plant seedling recruitment, we set up a field experiment where we manipulated the opportunity for plant–plant interactions through vegetation removal and introduction of willow transplants, the occurrence of herbivory through caging of plots, and then sowed 14 species into the plots. We replicated the experiment in three common alpine vegetation types (heath, meadow and Salix shrubland) and recorded seedling emergence and survival over five years. Strong effects of vegetation removal and substantial differences in recruitment among dominant vegetation types suggested important effects of local vegetation on the recruitment success of vascular‐plant seedlings. Similarly, herbivore exclusion had strong positive effects on recruitment success. This effect arose primarily via reduced seedling mortality in plots from which herbivores had been experimentally excluded and became noticeably stronger over time. In contrast, we detected no consistent effects of experimental willow shrub introduction on seedling recruitment. These results demonstrate that large and small herbivores can affect alpine plant seedling recruitment negatively by trampling and feeding on seedlings. Importantly, the effects became stronger over time, suggesting that effects of herbivory on seedling recruitment accumulates over time and may relate to recruitment phases beyond initial seedling emergence.